HYPOXIA-RESPONSIVE NANOPARTICLE FOR THERAPY AND IMAGING OF HYPOXIA-INVOLVING DISEASES - PARK, JAE HYUNG (2014)
The present invention relates to an amphiphilic polymer of which properties and a structure can be changed under a hypoxic condition, and to nanoparticles formed by self-assembly of the amphiphilic polymer. The hypoxia-sensitive nanoparticles according to the present invention selectively release a treating agent under a hypoxic condition and thus can be applied to a selective diagnosis and a selective treatment of diseases accompanied by hypoxia. Especially, with respect to the treatment of cancer, the hypoxia-sensitive nanoparticles can release the treating agent only in response to a targeted tumor and thus can minimize side effects and maximizes treatment effects.